Froebel dan Kognitif Anak Usia Dini: Telaah Teoretis tentang Peran Bermain Terstruktur dalam Meningkatkan Kemampuan Berpikir - Nelia Guswanti; Panggung Sutapa (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to examine the relevance of Friedrich Froebel's play theory to the cognitive development of early childhood and to formulate a conceptual model for the application of structured play in early childhood education. This study uses a literature review approach by analyzing scientific articles, books, and research findings from 2020–2025. The results of the study indicate that Froebel's concept of gifts and occupations functions as a concrete manipulative medium that can stimulate children's logical thinking skills, creativity, working memory, and representational abilities. Structured play allows children to explore basic mathematical concepts, patterns, spatial relationships, and problem-solving processes through direct experience. This article offers the